Genesis 2–3 as a Primal Scene for Weak Metaphysics - Heinrich-Ramharter, Esther (Interdisciplinary journal for religion and transformation in contemporary society, 2024)
In this paper, I examine the role that the biblical story of Adam and Eve, Genesis 2–3, plays for philosophers and biblical scholars who advocate a weak metaphysics. In particular, I discuss writings by Mark Glouberman, Richard Kearney and Gianni Vattimo. I examine the question of whether and in what sense Genesis 2–3 can be said to be a primal scene for weak thinking or weak metaphysics.